2020
DOI: 10.1101/2020.09.02.279778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calorie Restriction Prevents Age-Related Changes in the Intestinal Microbiota

Abstract: The effect of calorie restriction (CR) on the microbiome, fecal metabolome, and colon transcriptome of adult and old male mice was compared. Life-long CR increased microbial diversity and the Bacteriodetes/Fermicutes ratio and prevented the age-related changes in the microbiota, shifting it to a younger microbial and fecal metabolite profile in both C57BL/6JN and B6D2F1 mice. Old mice fed CR were enriched in the Rikenellaceae, S24-7 and Bacteroides families. The changes in the microbiome that occur with age an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Caloric restriction, for example, which is a nutritional intervention of reduced energy intake, has a strong influence on the gut microbiota (53,54). It has been found that caloric restriction can slow down age-related decline in the microbiome, increase both microbial diversity and Bacteroidetes/Firmicutes ratio, as well as change host microbial co-metabolites leading to a decrease in host lipid biosynthesis and an in increase fatty acid catabolism (55,56).…”
Section: Dietmentioning
confidence: 99%
“…Caloric restriction, for example, which is a nutritional intervention of reduced energy intake, has a strong influence on the gut microbiota (53,54). It has been found that caloric restriction can slow down age-related decline in the microbiome, increase both microbial diversity and Bacteroidetes/Firmicutes ratio, as well as change host microbial co-metabolites leading to a decrease in host lipid biosynthesis and an in increase fatty acid catabolism (55,56).…”
Section: Dietmentioning
confidence: 99%
“…However, CR delays aging mainly by mechanisms that regulate energy metabolism, decline oxidative damage and inflammation, modulate nutrient-sensing pathways, and enhance cytoprotection, as well as by epigenetic factors (Hearn et al, 2019;Hwangbo et al, 2020). Although the effects of CR on the intestinal microbiota have been reported, a direct proof that it exerts an aging-delaying effect by interfering with the microbiota has not been provided (Tan et al, 2019;Kurup et al, 2021). The CR remodeling of the intestinal microbiota mediates improvements in organismal metabolism that may contribute to delaying aging.…”
Section: Dietmentioning
confidence: 99%